Manajemen Strategis dan Proses Pemasaran(Studi Kasus: Cara Xpander Melakukan Perencanaan dan Proses Pemasaran) - Siregar, Aditya; Riofita, Hendra (Teewan Journal Solutions, 2025)
Strategic management is an important framework for formulating, implementing, and evaluating strategies used by companies to achieve long-term goals. In this case study, the focus is on the planning and marketing processes of the Mitsubishi Xpander, a successful automotive product in the Indonesian market. This research analyzes the strategic planning steps undertaken by Mitsubishi Motors to introduce and market the Xpander, starting from market analysis, segmentation, target market establishment, to product positioning. The marketing process applied includes various elements such as promotion, pricing, distribution, and product features tailored to consumer preferences in Indonesia. This study emphasizes the importance of synchronizing business and marketing strategies, as well as adapting to local market dynamics, which contribute to the success of the Mitsubishi Xpander in winning competition in the multi-purpose vehicle (MPV) segment. The method used is a case study with a library research. The results of this study indicate that a well-planned and strategic marketing approach can enhance competitiveness and market share of products in the automotive industry.